Tracing Preservice Teachers’ Professional Identities: Comparative Insights from Two Courses in Teacher Education - Ladachart, Luecha; Ladachart, Ladapa (Journal of Teaching and Learning, 2026)
Teacher education programs play a crucial role in developing preservice teachers’ professional identities. However, little is known about how this development unfolds during coursework. This study examines the development of preservice teachers’ professional identities within two courses delivered in the second and fourth years of a teacher education program in Thailand. Course A was theory-oriented, focusing on instructional methods and lesson planning aligned with the national curriculum. More practically, Course B emphasized the design and rehearsal of instruction. Participants included 36 preservice teachers majoring in physics (N = 6) and biology (N = 30), with most (27) enrolled in both courses under the study. A Likert-type questionnaire measured three components of professional identity—motivation, self-image, and self-efficacy— and was administered at the beginning and end of each course. Wilcoxon signed-rank tests compared pre- and post-course scores, and Friedman tests compared scores across four time points for participants who took both courses. Results reveal that only Course B contributed to the development of professional identity. However, because a decline occurred during and after Course A, no overall increase was observed by the end of the study. The findings highlight the value of practice-based experiences within coursework to strengthen preservice teachers’ professional identities.